Effectiveness of online and face to face problem based learning on the performance of diploma nursing students in a nursing course - Pardi, Kasmah Wati (Pusat Pengajian Sains Perubatan, 2013)
The use uf online problem-based Jeo.ming (PBL) is now gruwing rapid!}, ~:.•)leciolly in in.>titulions of higher h:aming: Nonetheless, evidence.an die effi:c:t)\ltmess of lhis karning mode, bo it the t;u:e,.ID-f'ace 11r. on!ir... mode, '-• Slifl lack.in!l, <speciBJiy its .. ~li'ectivt:11<15S in ~ing srudent engagement and lcaming.ach.ie-t amoog sll>dents. irr nuriing 4ahjccl; This s!udy aimed to examine !lie effecth'ell<n of bolh PBL delivery modes <lli the k:~l of student elllli'Semtlll and l"""lin.!l a<:hie~ement of dipklma nursing students, using the lec:tun: m~lhtx! as. the control variable. To .~~c:hieve Ibis obj~'" tM qua.<lCJqxrimental method ·wtiS empluyed o~ di~>loma nursing studenu in Uni\ltlsiti Sain.< Malaysia (uSr..l), Kelantan, alld Teclltro!~;~!} College of Bes!Bri (TCBJ, The USM studenli ~<>"Cre msde .. tfte intervention l!n1ups.a.[!li>up pan;cip.,ttd in flh~~-1<>-fllt:e PaL'(n ; H), while illlother IJTIIUP used rile online Pat (n ~ 35). Meanwhile. the rta students (n = 36) •Cied ... 1M control group lind "'""re rausht usin8 the I<C~ure method. Tht: el<pel'iment was c<lflducted tor 5 week>, after which the level of student. engagl:fTfent and learning achfevemenl fur lhc 11\re< ditfere:u delivery modes were measured. To U!>dC:ISLilnd tbc .'tfudo:nt's expt=ricnee .. ith tho three delivery IOOdes m<;>re dCCJ!Il', 21 srudentJ; (f;ke-to.face PBL, n ; 8; on.lin< PBL. n = 6; and lecum: method. n = 7). (OVering lhe ·three· melhllds of de!i¥r~y, were mterviewed. From tht: analysis done using the one.. way ANOVA. the mean .•core ofthe students in flice-to-face PBL Wll5· significantly high<r lhtlnlhal" of tire online PBt and lecwrc method in tenns of5tudent ~ent r.p <.OS; .t·11 ... ,1 -1~9\42) and learning ocl!ie~to!m<:nt (p < .05; l'j,, •• .~1 = 16JI70). The retult 11rthe intcrviC\01 rndicated that the main probl~s f!lt:ed by lhe onlim: PBL group were "dif!kult to upden1AJ!d anline.jnformatlon~ and ~c.al JM:flblcms JlS!Ioti;tted with the !nttmet. ~ This .~IJight have been the fact.Of that bas affected si:gnifitanlly ibe' eil'ect of online I'BL on stuthmt lllltl"gg:ll!e(IL and lelll'lling acliie\'l!nl02ll; JIW,Ierlheless. this' study. is Of the oplniun that if tbe online 'tudentswere gl \'crt tnon: e>Cj)OS~ on usong tfte onilne I'BL learning $}'Stem. ibeJ,.· is a possibifey that online J'BL «!Uid ~ beeo a.• goti<.lc if not better than. the lilce-Jo-mce PBL .. .!,; a n:corn~ndation fDr·lilture researd1, this stu!!) can be improved by using tillldotn ailtignmcnt, using a larger sample size, 8Jid mnro PBI. sessions., to ,CXJin:lilll' whether these Ylll'i~bles hRve any !nflu<nee on the difforential effects betw~en lhcc·to:>-fKe PBL and online f'Bl on studmt engagr:menr and. Itaming i!ohicvemm, In addttlor~ more in;depth qllalii.Btive studi~ need to be eorl!luctcd to explo"' the student <:nf!Jil!Cmtnt >ariabl., lnlhe different delivery' modes and its n:lationship wilh laming achie•=cm. to nbtiin a bener pic!""' ofrhe difference in the studoml pe7fcrmancc Ill: ross the fac.,.t<>-fa<esnd onlin~ PBL